2023
DOI: 10.1038/s41598-023-29567-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between shift work and the incidence of reflux esophagitis in Korea: a cohort study

Abstract: Shift work has adverse health effects such as diabetes, cardiovascular disease, sleep disturbance, depression, and breast cancer. Gastro-esophageal reflux disease (GERD) results in lesions such as reflux esophagitis (RE) and Barrett’s esophagus. This study investigated the association between shift work and RE. A cohort study was conducted with 140,553 participants who were followed up at least once from 2012 to 2018. Type of working and shift types were collected using standardized questionnaires. Esophagogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For bowel health, recent evidence has confirmed that circadian rhythms can influence the gut microbiota and microbial composition in terms of driving inflammation and hormonal responses ( Teixeira et al, 2020 ; Lotti et al, 2023 ). Population-based studies have also highlighted close relationships between circadian rhythms and bowel health, e.g., shift work appears to partly increase the risk of functional gastrointestinal disease ( Koh et al, 2014 ), peptic ulcer disease ( Knutsson and Bøggild, 2010 ), and reflux esophagitis ( Nam et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For bowel health, recent evidence has confirmed that circadian rhythms can influence the gut microbiota and microbial composition in terms of driving inflammation and hormonal responses ( Teixeira et al, 2020 ; Lotti et al, 2023 ). Population-based studies have also highlighted close relationships between circadian rhythms and bowel health, e.g., shift work appears to partly increase the risk of functional gastrointestinal disease ( Koh et al, 2014 ), peptic ulcer disease ( Knutsson and Bøggild, 2010 ), and reflux esophagitis ( Nam et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%